cis-acting elements in the lytic origin of DNA replication of Epstein-Barr virus. - Schepers, A (1993)
oriLyt, the cis-acting element of Epstein-Barr virus, mediates viral DNA replication in the lytic phase of the virus's life cycle. Oligonucleotide-directed in vitro mutagenesis of oriLyt plasmids allowed the identification of two noncontiguous components within the complex structure of oriLyt. Both components were indispensable for DNA replication of this origin. The upstream component colocalized with the promoter of the viral BHLF1-encoding gene, and mutants affecting DNA replication affected RNA transcription, too. The second component crucial for oriLyt function was determined to be 40 bp long and positioned approximately 530 bp downstream. It was dispensable for transcriptional transactivation but it was absolutely required for replication. Thus, the overall design of oriLyt has striking similarity to multipartite regulatory elements of transcription, consisting of proximal promoters and distal enhancers, but special elements are exclusively dedicated to DNA replication.